Climate-Smart Farming Practices: A Pathway toward Sustainable Global Agriculture - B. A, Abdusattorov; Y. B., Yusupov (American Journal of Biodiversity, 2025)
Climate-smart farming (CSF) represents a transformative approach to global agricultural development that integrates productivity, adaptation, and mitigation goals to address the escalating challenges of climate change. Agriculture contributes approximately 25% of global greenhouse gas (GHG) emissions, yet it remains the most climate-sensitive economic sector. Increasingly frequent droughts, floods, and heatwaves threaten the livelihoods of nearly 2.5 billion people dependent on farming. This paper examines the principles, technologies, and socio-economic dimensions of climate-smart agriculture (CSA), highlighting how precision farming, water-efficient irrigation, soil conservation, renewable energy, and digital innovations can improve resilience and sustainability. The article also explores the economic implications of CSF adoption and the institutional frameworks necessary for large-scale implementation. It concludes that achieving climate-smart agriculture globally requires integrated policy support, sustainable financing, and cross-sectoral collaboration to ensure equitable and resilient food systems.